High speed imaging of micro-sized droplet jetted on surface with wettability pattern - Lim, Chun Yee (2014)
Experimental results based on high speed imaging of micro-sized droplet jetted on a hydrophobic surface with hydrophilic lines are presented. The effects of the hydrophilic line and the initial impact offset distance from the line on the droplet spreading behaviour are studied. Two distinct processes have been identified, namely the centering and conforming processes. During the centering process, the droplets which impinge at a certain offset distance from the center of the hydrophilic lines migrate towards the center of the line. A droplet with a larger offset distance experiences a slower centering process. This conforming process involves droplets elongate along the hydrophilic line, causing the droplet to conform to the wettability pattern. The outcome of this study can be applied to inkjet printing process for the enhancement of material deposition accuracy and tolerance of printed micro-sized features.